Decarbonylated cyclophilin A Cpr1 protein protects Saccharomyces cerevisiae KNU5377Y when exposed to stress induced by menadione - Kim, Il-Sup (Springer Netherlands, 2010)
Cyclophilins are conserved cis–trans peptidyl-prolyl isomerase that are implicated in protein folding and function as molecular chaperones. The accumulation of Cpr1 protein to menadione in Saccharomyces cerevisiae KNU5377Y suggests a possibility that this protein may participate in the mechanism of stress tolerance. Stress response of S. cerevisiae KNU5377Y cpr1Δ mutant strain was investigated in the presence of menadione (MD). The growth ability of the strain was confirmed in an oxidant-supplemented medium, and a relationship was established between diminishing levels of cell rescue enzymes and MD sensitivity. The results demonstrate the significant effect of CPR1 disruption in the cellular growth rate, cell viability and morphology, and redox state in the presence of MD and suggest the possible role of Cpr1p in acquiring sensitivity to MD and its physiological role in cellular stress tolerance. The in vivo importance of Cpr1p for antioxidant-mediated reactive oxygen species (ROS) neutralization and chaperone-mediated protein folding was confirmed by analyzing the expression changes of a variety of cell rescue proteins in a CPR1-disrupted strain. The cpr1Δ to the exogenous MD showed reduced expression level of antioxidant enzymes, molecular chaperones, and metabolic enzymes such as nicotinamide adenine dinucleotide phosphate (NADPH)- or adenosine triphosphate (ATP)-generating systems. More importantly, it was shown that cpr1Δ mutant caused imbalance in the cellular redox homeostasis and increased ROS levels in the cytosol as well as mitochondria and elevated iron concentrations. As a result of excess ROS production, the cpr1Δ mutant provoked an increase in oxidative damage and a reduction in antioxidant activity and free radical scavenger ability. However, there was no difference in the stress responses between the wild-type and the cpr1Δ mutant strains derived from S. cerevisiae BY4741 as a control strain under the same stress. Unlike BY4741, KNU5377Y Cpr1 protein was decarbonylated during MD stress. Decarbonylation of Cpr1 protein in KNU5377Y strain seems to be caused by a rapid and efficient gene expression program via stress response factors Hsf1, Yap1, and Msn2. Hence, the decarbonylated Cpr1 protein may be critical in cellular redox homeostasis and may be a potential chaperone to menadione. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s12192-010-0215-9) contains supplementary material, which is available to authorized users.